1966
DOI: 10.1113/expphysiol.1966.sp001852
|View full text |Cite
|
Sign up to set email alerts
|

The Node of Ranvier in the Central Nervous System

Abstract: The axolemma of myelinated nerve fibres of the central nervous system has been examined both at nodes and in the paranodal region. In the paranodal region, the outside of the axolemma is separated from the outer surface of the plasma membrane bounding the inner aspect of the paranodal cytoplasm by a distance of only 25-30 A, so that the two membranes form a complex. In longitudinal sections, a periodicity may be observed within this complex. It has been shown that this is mainly due to the form of the outer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

1968
1968
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(50 citation statements)
references
References 14 publications
2
47
0
1
Order By: Relevance
“…However, they regarded these axons as myelinated axons which were cut at the node of Ranvier, because of the presence of electron dense granular material beneath the axolemma, which was thought to be a characteristic of an axon at a node of Ranvier by PETERS (1966). According to the present observation, the Table 1.…”
Section: Discussionmentioning
confidence: 97%
“…However, they regarded these axons as myelinated axons which were cut at the node of Ranvier, because of the presence of electron dense granular material beneath the axolemma, which was thought to be a characteristic of an axon at a node of Ranvier by PETERS (1966). According to the present observation, the Table 1.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, other ankyrin-binding proteins are also localized at the node, including isoforms of neurofascin and NrCAM (Davis et al, 1993(Davis et al, , 1996, ankyrin-binding cell adhesion molecules related to L1 (for review, see Hortsch, 1996). Ankyrin itself is localized at the 1-to 2-m-size nodal axonal plasma membrane (Kordeli et al, 1990) and is a component of the electron dense undercoating observed beneath the nodal membrane (Peters, 1966;Ichimura and Ellisman, 1991). Ankyrins are a family of spectrin-binding proteins that associate with diverse integral proteins, including ion channels, calcium-release channels, and cell adhesion molecules, and link these proteins to the spectrin-based membrane skeleton (for review, see Bennett and Gilligan, 1993;Lambert and Bennett, 1993).…”
Section: Abstract: Node Of Ranvier; Cell Adhesion Molecules; Ankyrinmentioning
confidence: 99%
“…In this way, the structural complexes may be related to the so-called gap junctions (18) which represent the morphological correlates for the low resistance junctions that serve as sites of electrotonic coupling between cells (14). The existence, at the surfaces of the apposed membranes, of a lattice formed by globules or particles closely packed in a hexagonal array is, at present, the well-known ultrastructural feature of the gap junction (17,18). These junctions have also been pointed out in nerve tissue of vertebrates and invertebrates (15,23).…”
Section: Villegas and Villegas Glycoside-sensitive Structures In Squimentioning
confidence: 99%
“…These postsynaptic densities have been related to the sites where permeability changes occur (4). The opaque axoplasmic material of the nodes of Ranvier has been thought to be related to specialized zones of membrane permeability (5), to areas of activity (17), or to diffusion barriers (I). A dense layer of fine granular material undercoating the plasma membrane of the axon initial segment, resembling that found at the node of Ranvier, has also been described in different neurons (13,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation